The sublime and its environmental implications - Dönmez, Damla. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
This research is about the concept of sublime and its environmental ethical implications. I claim that sublime, as an aesthetic concept, is helpful to give us moral motivation for the preservation of nature. We have a peculiar dual relation with nature; it is both an Other and an extended Self. Hence, I claim sublime is a specific aesthetic concept that can endow us with ethical tools to face this peculiar dual relation with its character of causing both pleasure and displeasure. First, with its displeasure effect, it can point to the otherness of Nature and induce (1) humility and (2) respect and second, with its pleasurable effect, it can lead to a concept of selfhood that can expand to include all nature which would create (1) attentiveness/sensitivity and (2) compassion/love. The objections against sublime fall into five different categories, (1) practical, it is not functioning as it promises, (2) epistemological, it is epistemologically inaccessible, (3) historical, it is an outdated concept that has no relevance in the contemporary agenda, (4) metaphysical, sublime is same with religious experience and (5) ethical, sublime is self-regarding, anthropocentric. Against these I defend sublime that (1) it is a humble concept not aiming to solve all the environmental problems once and for all but only trying to enrich our aesthetic and ethical agenda, (2) sublime is a concept of language trying to bridge the gap between the world and us, (3) nature is the original sublime and it can never be exhausted, (4) sublime is aesthetic and secular, with no necessary dependence on a divine being and (5) sublime is not anthropocentric, centered on humans, but anthropogeneric, generated by humans.
Keywords: Sublime, The.; Environmental ethics.